Effect of Work Culture on Teacher Performance in Public High Schools in Kendari City - La Ode Amaluddin; Jamiluddin Jamiluddin (Budapest International Research and Critics University, 2022)
This study aims to analyze and describe the presence or absence of effect of work culture on teacher performance in Public High Schools in Kendari City. This research is a research that uses a quantitative approach. The population of this study was 470 teachers, with a total sample of 216 teachers. The sample was determined by using probability sampling technique using proportional stratified random sampling. Data analysis technique with structural equation modeling is used to test the hypothesis. The results showed that the value of C.R=0.039 with probability=0.969 (p>0.05). So, it can be concluded that work culture has no positive and significant effect on teacher performance in Public High Schools in Kendari City.